(untitled) (Italiano LinguaDue, 2016)
Le etimologie delle due edizioni del Vocabolario milanese-italiano di Francesco Cherubini, tratte da fonti che vanno dal Varon milanes al Muratori, per un verso mostrano le debolezze tipiche della fase precedente la scoperta del metodo comparativo, soprattutto quando si risale al greco e al latino, per un altro sono lodevoli per la cautela adoperata in molti casi e appaiono tuttora utili quando si rimonta a lingue straniere coeve o quando la spiegazione della parola si apre all’etnografia. L’articolo si chiude con una spigolatura sulla voce mazzacronegh. Cherubinian etymologies The etymologies of the two editions of the Milanese-Italian dictionary by Francesco Cherubini, drawn from sources ranging from Varon Milanes to Muratori, on the one hand show the typical weaknesses of the previous stage the discovery of the comparative method, especially when going back to Greek and Latin. On the other hand, these volumes are commendable for caution used in many cases and still seem useful when reassembling contemporary foreign languages or when the explanation of a word involves ethnography. The article ends with an explanation of the entry “mazzacronegh”.